Analysis of marketing strategies and advanced retail sales processes to improve Company A’s position in the segment - Rouse, Tyler (Kansas State University, 2018)
In recent years across the United States, product sales have seen a downward trend when compared to the robust sales figures posted around the 2010 time period across the major players in the product manufacturing space. Due to depressed commodity prices, large product sales have caused a lot of the dealers to shift in its prioritization of sales from a predominant large product business model, to a more diverse large product and small product strategy portfolio to stay profitable amidst economic headwinds. This study will look into ways that the Company A dealer channel could pivot their internal processes around targeting customers who are engaged in the purchase funnel of purchasing small products and how Company A could change the way the company equips their trusted dealer channel to combat competition in this segment. This study will examine new strategies that may be executed through the Company A dealer network and their subsequent retail showrooms to increase sales by focusing on key product differentiating characteristics, unique technical selling points, dealer facility positioning in high potential Metropolitan Statistical Areas, and new retail digital marketing technologies that should be leveraged throughout the sales process to improve market share. Company B is considered to be the primary rival competitor in this small product market, as this firm is one of the fiercest competitors to Company A’s quest for total product sales superiority. This study conducted a mixed method survey to ascertain what areas of marketing and promotional assistance should be prioritized by Company A, to outfit the company’s existing dealer channel with the right tools to combat Company B and other competitors in the U.S. small product market. Additionally new retail showroom technologies and strategies were based upon existing market research studies, focused on which customer’s and product characteristics were the most impactful for positively impacting small product sales in the United States.
Keywords: Marketing strategies; Retail sales; Sales process; Customer perception; Customer segmentation; Purchase funnel